The Cattle Frontier and the Melinis Minutiflora P. Beauv. (POACEAE):: Environmental History and Grassland Landscapes in the 19th Century’s Brazilian Cerrado - Silva, Sandro Dutra; Mateus, Rosimeire; Braz, Vivian; Peixoto, Josana (Sustainability in Debate, 2015)
This article offers a discussion about a range of exotic grasses - most of them originally from Africa- present in the Brazilian Cerrado biome. Cattle-ranching was the main economic activity in Goiás during the 19th and first half of the 20th centuries. The Cerrado´s grasslands favored the settlement of a cattle-ranching community, including their herds and farms. Through the lenses of the environmental history of grasses and cattle-ranching, this article seeks to analyze the relation between society and nature in the savannas of the Brazilian central plateau in the 19th and first half of the 20th centuries. The presented discussion links the approaches of botany and environmental history to analyze the transformation of the local landscape due to anthropogenic activities. The study follows the process of introduction of exotic grasses in the Cerrado biome, highlighting the historical records of native African grasses (capim-gordura/Melinis minutiflora) and their role in the expansion of livestock production in Goiás.